Congenital amegakaryocytic thrombocytopenia: three case reports from patients with different clinical diagnoses and somatic abnormalities. Issue 3 (April 2015) - Yıldırım, Ayşen Türedi; Güneş, Burçak Tatlı; Oymak, Yeşim; Yaman, Yöntem; Özek, Gülcihan; Cartı, Özgür; Yeşilipek, Akif; Vergin, Canan
Abstract : The congenital amegakaryocytic thrombocytopenia (CAMT) is a syndrome characterized by preservation of granulocytic and erythroid cells during genesis, with a gradual or progressive decrease in the number of megakaryocytic series of cells in the bone marrow. At later times, most patients develop aplastic anemia. It is important to rule out specific causes of thrombocytopenia that develop in the early stages of CAMT. Typically, there are no specific somatic abnormalities that accompany this deadly disease. Here we present three CAMT cases that presented with different clinical diagnoses, with various physical anomalies in two of those cases. The first patient was examined because of a cytomegalovirus infection. The second patient had been referred with a suspected neonatal alloimmune thrombocytopenia, whereas the third patient presented with chronic immune thrombocytopenic purpura. Subsequently, all three patients were diagnosed with CAMT. Two of the patients had physical anomalies. In particular, the first patient had a duplex urinary system. To our knowledge, this is the first patient with CAMT to have a duplicated collecting sysem. The second patient had a secundum atrial septal defect, an atypical facial appearance, and growth retardation. Since CAMT could also be observed outside the neonatal period, the differential diagnosis for thrombocytopenia should be considered for all age groups. Moreover, it should be considered that CAMT may also be accompanied with somatic abnormalities.